2016
DOI: 10.1007/s10565-016-9357-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of memory CD4+ T cells’ signal transducer and activator of transcription (STATs) functional shift on cytokine-releasing properties in asthma

Abstract: The long-lived, antigen-specific memory CD4 T cells, rather than PBMCs or peripheral lymphocytes, might be the ideal T cell subset candidates for analyzing the endotype of asthma. Memory CD4 T cells exhibiting a shift in STAT phosphorylation and specific cytokine-releasing profiles have the potential to facilitate the understanding of disease heterogeneity and severity, allowing the more personalized treatment of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
7
0
3
Order By: Relevance
“…Asthma is a chronic inflammatory airway disease, and oxidative stress may be involved in its pathogenesis. Chronic airway inflammation, airway smooth muscle contraction and bronchial hyperreactivity are three major characteristics of the pathogenesis of asthma [ 80 82 ]. Considerable evidence has shown that ROS are involved in these three processes.…”
Section: Ros-related Lung Diseasesmentioning
confidence: 99%
“…Asthma is a chronic inflammatory airway disease, and oxidative stress may be involved in its pathogenesis. Chronic airway inflammation, airway smooth muscle contraction and bronchial hyperreactivity are three major characteristics of the pathogenesis of asthma [ 80 82 ]. Considerable evidence has shown that ROS are involved in these three processes.…”
Section: Ros-related Lung Diseasesmentioning
confidence: 99%
“…In conclusion, IRF1 could be a key gene for glucocorticoids resistance of NA. Signal transducer and activator of transcription 1 (STAT1) regulates production of Th1 cellspecific cytokine to alter inflammatory response and it is a key mediator in IFNγ signaling (Chen et al, 2017;Zhang et al, 2018). Several studies have shown that STAT1 participants in the differentiation of Th17 cells and it may become a key gene in the development of NA (Villarino et al, 2010;Kimura et al, 2008;Nielsen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Исследования, проведенные на взрослых лицах, отмечают повышенное содержание Т-клеток памяти у пациентов с БА в сравнении со здоровыми лицами, которое ассоциировано со степенью тяжести данного заболевания [2]. Также повышение количества Т-клеток памяти связывают с изменением их функциональной активности и существованием различных эндотипов БА [4]. Количество Tnaïve клеток (CD4 + CD45R0и CD8 + CD45R0 -), по данным других авторов, не изменяется при БА, что согласуется с нашим исследованием [2,27].…”
Section: Discussionunclassified
“…По данным литературы, точная роль различных субпопуляций Т-клеток памяти в патогенезе БА не установлена. Так, в проведенном недавно исследовании, наряду с функциональными изменениями Т-клеток памяти, было выявлено повышенное содержание TcmCD62L + и TemCD62L + в CD4 + клетках периферической крови у пациентов с БА [4]. В другой работе было показано, что у взрослых пациентов с БА, вне зависимости от формы и степени тяжести заболевания, повышается число CD4 + Tcm, но не CD4 + Tem по сравнению с донорами, что не подтверждается данными нашего исследования [28].…”
Section: Discussionunclassified
See 1 more Smart Citation